DISPARITY OF JUDGES' DECISIONS REGARDING CRIMINAL OFFENSES THEFT OF PLANTATION PRODUCTS - Hengki Syahyunan; Yanto Zelibu; Putri Habibah Siregar (Universitas Labuhanbatu, 2024)
The disparity in the application of the law against perpetrators of theft of plantation products is a law enforcement problem that must be resolved in order to create a sense of justice, certainty and legal benefits. The purpose of this research is to be a reference for law enforcers in applying fair, certain and useful rules. This research is an analytical descriptive research with a type of qualitative research that examines and analyzes references to journals, books, laws and regulations, and considerations of judges' decisions. The clear conclusion is that there is a disparity in the perspective of judges in imposing legal decisions on perpetrators of theft of plantation products. The disparity in judges' decisions in plantation theft cases reflects various challenges in the justice system. Factors such as variations in evidence, differences in legal interpretation, local social influences, and the quality of law enforcement play an important role in creating uncertainty. To achieve better justice and consistency in decisions, reforms in the justice system are needed, including improving the quality of law enforcement, especially judges. Thus, it is hoped that justice for victims can be achieved, and the justice system can be more trusted by the community.Keywords: Disparity; Plantation Products; Theft;